PENGARUH PENGAPLIKASIAN FOUNDATION SEBAGAI DASAR MENGGUNAKAN TEKNIK CUT CREASE TERHADAP HASIL RIAS WAJAH PENGANTIN SUNDA PUTRI - Atasya Fadhilah Afifah; Rahmiati Rahmiati (Jurnal Tata Rias dan Kecantikan, 2022)
Cut crease is usually applied with light colors to strengthen the eyes. Foundation application technique as the basis of using cut crease with eyeshadow application to emphasize the folds of this eye will give a greater dimension and eye effect. This study aims to a) Analyze the results of application without foundation as the basis of using cut crease techniques against the makeup results of Sundanese Brides, b) Analyzing the results of foundation application as the basis of using cut crease techniques against the makeup results of Sundanese Brides and c) Analyzing the differences in the influence of application without foundation and with foundation as the basis of using cut crease techniques against the makeup results of Sundanese Princess brides.This type of research is pre-experimental design. The population of this study is a student of Padang State University with an age range of 19 years to 23 years, has a close to normal eye shape and has a normal skin type that has no allergy to cosmetics with 6 samples and 7 panelists. Data retrieval technique is purposive sampling method. Data analysis techniques use descriptive statistic techniques with percentages and t-tests to describe hypothesis tests. Based on the results of the study seen from 3 people sampled in the group without foundation application of the aspect of sharpness of eyeshadow color obtained an average of 2.1414 categories less clear, aspects of the impression of eyelid shape obtained an average of 2.3329 categories less formed and aspects of favorite observers averaged 2.1886 categories less likes. Furthermore, the results of the study were seen from 3 people sampled in the group with foundation application of the aspect of sharpness of eyeshadow color obtained an average of 3.5729 categories very clearly, aspects of the impression of eyelid shape obtained an average of 3.2843 categories formed and aspects of favorite observers averaged 3.1886 categories likes. There is a difference in the sharpness of the eyeshadow color without foundation and with foundation, the value p = 0.000 (p<0.05), there is a difference in the impression of the shape of the eyelids without foundation and with foundation, the value p = 0.003 (p<0.05) and there is a difference in the preference of observers without foundation and with foundation, the value p = 0.002 (p<0.05). It is recommended for makeup and beauty students to be able to apply foundation as the basis of using cut crease technique to make up sundanese bride's makeup.